Analisis Model Pembiyaan Dana BOS dan BOP pada Lembaga Pendidikan yang Pernah Diterapkan di Indonesia - Hadi, Samsul (Lembaga Yasin AlSys, 2021)
This study aims to describe the financing model for BOS Funds and BOM/BOP in educational institutions that have been implemented in Indonesia. The research used descriptive qualitative. Data collection techniques using observation, and document study. Research results (1). The education financing system in Indonesia is borne by the central government, regional governments and the community. The education financing models in Indonesia are sourced from a). Central Government and Local Government in the form of BOS Fund (School Operational Assistance), BOP (Education Operational Assistance) and b). Parents / Guardians of Students. The types of expenditures by parents/guardians for education include: 1) Base Fee, 2) Monthly Tuition / Tuition Fees, 3) Mid-Semester Examination Fees, 4) End of Semester Examination Fees, Extracurricular Activities Fees, 6) Practicum Activities Fees , 7) Purchase of Textbooks / LKS, 8) Purchase of School Uniforms, 9) Expenses for Field Trips / Mental Development / Retreats, 10) Social Donations, 11) Other expenses. (2) Analysis of education financing models that have been applied in Indonesia such as BOS/BOP and others. In the government regulations for the period of disbursement and reporting of School and Madrasah and PAUD BOS funds which the authors have classified, there are advantages and disadvantages in their implementation. In the initial period there was the involvement of Provincial and District BOS Managers so that in the process of filing the disbursement and reporting of BOS Funds they could be guided and supervised directly. Meanwhile, in the latest regulation, the process of filing for disbursement and reporting of BOS Funds is directly guided and fostered by the Central BOS manager.